Creative, Antagonistic, and Angry? Exploring the Roots of Malevolent Creativity with a Real‐World Idea Generation Task. (12th December 2020) - Perchtold‐Stefan, Corinna M.; Fink, Andreas; Rominger, Christian; Papousek, Ilona
Abstract: Research is currently witnessing more investigations into malevolent creativity—creativity that is used to intentionally harm others. Inspired by previous methods to measure malevolent creativity, in the present study, we introduce a real‐world behavioral task designed to capture individuals' capacity for using creativity for the purpose of attaining malevolent goals in response to everyday, provocative situations. In a sample of 105 students, we found malevolent creativity positively correlated with fluency in conventional creative ideation, as well as with self‐reported typical malevolent creativity behavior in daily life. Moreover, performance on the malevolent creativity task showed positive correlations with the maladaptive personality trait of antagonism (PID‐5) as well as individuals' state anger at the beginning of the experiment. Further, our multiple regression analysis revealed that conventional creative ideation, antagonistic personality, and state anger all explained unique, non‐overlapping variance in the capacity for implementing malevolent creativity. As a whole, these findings suggest that different cognitive and affective factors, along with specific personality traits may each contribute to the expression of malevolent creativity in distinct ways. Future investigations striving to further decode the destructive potential of individuals toward others may benefit from this validated behavioral measurement approach to malevolent creativity.